Protocol for mapping the heterogeneous dendritic cell network across the murine tissue landscape via high-dimensional flow cytometry - Amon, Lukas; Seichter, Anna; Vurnek, Damir; Tchitashvili, Giorgi; Heß, Isabel; Heger, Lukas; Lehmann, Christian; Dudziak, Diana (STAR Protocols, 2024)
Dendritic cells (DCs) populate nearly all tissues and represent the central orchestrators of immunity. Here, we present a protocol for the mild but efficient preparation of single-cell suspensions from multiple murine tissues and the downstream analysis of the DC network via high-parameter flow cytometry. Additionally, we provide evaluation strategies that facilitate the stringent separation of the DC family from other myeloid cells, particularly macrophages and monocytes, and include an in-depth assessment of DC-intrinsic heterogeneity. For complete details on the use and execution of this protocol, please refer to Amon et al.1
CRIS-Team Scopus Importer:2024-07-19
Keywords: Cell Biology; Cell isolation; Flow Cytometry; Immunology; Single Cell